"You're Used To Being The One That Can Fix Things…": A Qualitative Snapshot of Colorectal Surgeons During COVID-19. Issue 12 (December 2020) - Byrnes, Mary E.; Varlamos, Christopher J.; Rivard, Samantha J.; Duby, Ashley A.; De Roo, Ana C.; Hibbard, Clarice E.; Callow, Matthew J.; Dimick, Justin B.; Byrn, John C.
Abstract : Supplemental Digital Content is available in the text.